2015
DOI: 10.1159/000381183
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Loading in Speaking a Foreign Language

Abstract: Aims: This study investigated whether speaking a foreign language affects the subjective notions of vocal fatigue, and whether acoustic measurements reveal a higher vocal loading. Methods: The speech samples of 20 native Finnish-speaking and 23 native English-speaking subjects were recorded in Finnish and in English. From the speech samples, fundamental frequency, equivalent sound level, total duration of voiced speech, speech rate, alpha ratio and L1-L0 level difference were analyzed. Vocal doses were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
3
1
2
Order By: Relevance
“…Because of this, the same test was done separately for the male and female participants. And again, the results of this study did not correspond to the results of the study of Järvinen and Laukkanen (2015). For English, the female participants did change their fundamental frequency significantly (t(4) = 4.37, p = 0.01199),…”
Section: Foreign Language Influences On Fundamental Frequencycontrasting
confidence: 93%
See 1 more Smart Citation
“…Because of this, the same test was done separately for the male and female participants. And again, the results of this study did not correspond to the results of the study of Järvinen and Laukkanen (2015). For English, the female participants did change their fundamental frequency significantly (t(4) = 4.37, p = 0.01199),…”
Section: Foreign Language Influences On Fundamental Frequencycontrasting
confidence: 93%
“…Another result by Järvinen and Laukkanen (2015) was that women adapt their fundamental frequency to the foreign language more than men. But again the present study found something different.…”
Section: Foreign Language Influences On Fundamental Frequencymentioning
confidence: 99%
“…A sixth limitation is related with the difference in acoustics voice parameters among different languages (e.g. the amount of voiced speech (% Dt)) can be related to the fact that the speech rate and the word duration are different in the languages [57]. In this meta-analysis, we included studies performed in countries with Germanic languages, except in Bottalico et al and Cantarella et al who had their investigations in Italian (Latin language).…”
Section: Discussionmentioning
confidence: 99%
“…Yksi selitys muuttuneelle kehityskululle voi olla englannin kielen lisääntynyt käyttö. On nimittäin havaittu, että syntyperäiset suomenkieliset puhujat nostavat puhekorkeuttaan puhuessaan englantia ( Järvinen, Laukkanen & Aaltonen, 2013). 2 Laukkanen ja Waaramaa (2020) kysyvätkin, voisivatko globaali viihdeteollisuus ja englannin valta-asema saada aikaan sen, että suomalaisten F0 olisi lähtenyt nousuun.…”
Section: Havainnot Puheäänenunclassified
“…On tosin huomautettava, että jo pelkästään vieraan kielen puhumiseen liittyvä jännitys tai epävarmuus voi saada aikaan F0:n nousua( Järvinen, Laukkanen & Aaltonen, 2013). Toisaalta samassa tutkimuksessa englanninkielisillä puhujilla F0 ei noussut suomea puhuttaessa -joskaan ei liioin madaltunut.…”
unclassified